ENVIRONMENTAL EDUCATION IN SCHOOLS AND THE EDUCATOR AS A CRITICAL SUBJECT OF THEIR PERFORMANCE - Santos Freitas Leboreiro, Márcia; Faria Lemes, Autieres (Journal of Interdisciplinary Debates, 2023)
In the last decades of the 20th century, concerns about the Environment have intensified. Various sectors of society already realize the importance of knowledge and sustainable growth for a better environmental balance on the planet we live on. The environmental issue has been considered increasingly urgent for society because the future of society depends on the relationship between man and nature in biological balance. Environmental Education, understood as an educational and dialogical process, which must contemplate the epistemic subject, in this approach must be worked in a way that privileges the individual for the construction of an ethical morality capable of ensuring a stable relationship with the socio-environmental atmosphere.